Sistem Pendukung Keputusan Pemberian Tugas Belajar Pegawai Negeri Sipil - Tukan, Ewaldus Ambrosius; Kusrini, Kusrini; Al Fatta, Hanif (Jurnal Informa : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The awarding of study assignment scholarships for civil servants is carried out to improve professional competence and professional skills, taking into account several aspects, namely (1) Service Period, (2) Age, (3) Achievement, (4) Performance, (5) Discipline Knowledge, and (6) Good Behavior, which was initially used in the scholarship selection process for study assignments without calculation.Utilization of a decision support system was chosen as a solution to overcome problems in selecting scholarships for study assignments for civil servants within the scope of local government at the district level so as to minimize the occurrence of errors in giving these learning assignments to civil servants using the Multifactor Evaluation Process (MFEP) method. By making multi-factor decisions, subjective and intuitive decision making can be avoided.The results of the study obtained an alternative with the highest total evaluation factor weight at 14.95 and it was concluded that the calculation of the selection of scholarships for study assignments using a decision support system obtained results that could be accounted for in supporting the decision making carried out by the regional head at the district level concerned.